Sputum conversion and treatment success among tuberculosis patients with diabetes treated under the Tuberculosis Control Programme in an Urban setting in South India - Velayutham Banurekha; Tarun Bhatnagar; Swaminathan Savithri; Natarajan Dinesh Kumar; Boopathi Kangusamy; Sanjay Mehendale (Wolters Kluwer Medknow Publications, 2017)
Background: Studies from India on sputum conversion and tuberculosis (TB) treatment outcomes among TB patients with diabetes are limited. Objective: The objective of this study is to estimate the proportion of sputum smear conversion and successful treatment outcomes among diabetic-TB patients treated under Revised National TB Control Programme (RNTCP). Methodology: Information on TB disease, diabetes, sputum conversion, and treatment outcomes were collected from treatment cards of adult TB patients (age >18 years) treated in the District TB Centre TB Unit, Tiruchirapalli, Tamil Nadu from July 1, 2014, to October 31, 2015. Results: Diabetes was documented in 163 (14%) of 1131 TB patients. Sputum conversion was in 107 (94%) of 114 smear positive-TB patients. Successful TB treatment outcome was in 116 (85%) of 136 patients and 107 (86%) of 124 new TB patients. Conclusion: Sputum conversion was as per RNTCP target while treatment success rate among the new TB patients with diabetes was suboptimal.